How Health Systems World-wide Fail Type 2 Diabetics - Abdo S. Yazbeck; Son Nam Nguyen; Maria-Luisa Escobar (Health Systems & Reform)
For over 50 years, health systems the world over have failed people with type 2 diabetes mellitus (T2DM). The WHO documents a quadrupling of people with diabetes in a 34-year period to 422 million in 2014, the overwhelming majority of whom were T2DM. This happened despite extensive scientific literature on the causes of, as well as proven treatments for, this disease. Using a health systems prism to review the extensive medical and nutritional T2DM published research, we identified three main shortcomings of health systems in T2DM: (i) failure in early detection; (ii) failure in understanding the actionable lifestyle drivers; and (iii) subsidizing the causes of the disease. Although small-scale success stories in T2DM control exist, the lack of documented evidence of any country-wide health system’s successful attempt to address this epidemic is alarming. The immense and ever-growing health and economic burdens of T2DM should provide all the motivation needed for national and global efforts to counteract the political-economy constraints standing in the way of successful whole-of-system approaches to T2DM.